2015
DOI: 10.1136/bcr-2014-206288
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis of the native aortic valve caused byLactobacillus jensenii

Abstract: SUMMARYLactobacilli are Gram-positive anaerobic rods or coccobacilli, commonly found as commensals in human mucosa. Rarely, they can cause serious infections such as infective endocarditis (IE), and the most frequently implicated species causing serious infections are L. casei and L. rhamnosus. IE caused by Lactobacillus jensenii is very rare, with only six reported cases so far, to the best of our knowledge. We present a case of native aortic valve endocarditis caused by L. jensenii, complicated by root absce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Lactobacillus species are a rare cause of infective endocarditis, comprising <0.5% of cases [ 4 , 11 , 12 ]. Despite their low virulence, certain species of the genus can adhere to endovascular surfaces and cause infection [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus species are a rare cause of infective endocarditis, comprising <0.5% of cases [ 4 , 11 , 12 ]. Despite their low virulence, certain species of the genus can adhere to endovascular surfaces and cause infection [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus is commonly seen as an additive in many yogurts, fermented foods, and probiotics marketed to maintain health and prevent illness [11] . Pathogenesis is related to the bacteria’s ability to produce enzymes that break down human glycoproteins allowing for early colonization, adherence, and biofilm formation, ultimately leading to bacterial translocation across the gut mucosa [12] , [13] Literature review revealed multiple reported cases of Lactobacillus endocarditis, but only six cases of infective endocarditis attributed to Lactobacillus jensenii as the primary pathogen [1] , [14] , [15] , [16] , [17] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Lactobacillus jensenii , a species used for food fermentation, has been recorded to cause endocarditis in a patient with underlying conditions (Patnaik et al . ). Rare clinical isolates were also described in the genus Leuconostoc , whose species are applied across a variety of food production processes, such as a bloodstream infection due to Leuconostic lactis in an elderly woman with pneumonia and abdominal infection (Yang et al .…”
Section: Introductionmentioning
confidence: 97%